Yes lives in the land of no : a tale of triumph over negativity - Gallagher, B. J. (Barbara J.), 1949- (BK life book., 2006)
In this wise little parable, readers follow a narrator who ventures into the Land of No in search of Yes. He learns by watching others as they search, flounder, and eventually become disillusioned by seemingly inevitable rejection. Though each of the characters is passionate about their cause, they all fail because they do not effectively deal with the obstacles they face. By watching their mistakes, the narrator learns how to persevere despite the No's, and ultimately succeeds in finding the elusive Yes. Through his journey, readers discover how they, too, can persist in the face of frequent No's. Both the No's uttered by those around them and, even more significantly, the No's sounded by their own inner voice. The parable comes complete with quizzes, tips, checklists, and how-to strategies that enable readers to achieve goals and deal with rejection, roadblocks, and negativity.